Relação entre a ingestão de micronutrientes, perfil de citocinas plasmáticas e expressão dos genes IL-6. IL-10 e TNF-α na obesidade mórbida - Campos, Joara de Paula [UNESP] (2015)
Obesity is a multifactorial disorder involving hereditary and environmental factors and lifestyle, its adverse effects are not only social or psychological, but are also related to the presence of comorbidities such as hypertension, type 2 diabetes and cardiovascular disease, being considered by World Health Organization as a global epidemic. Obesity is defined as a disease associated with chronic low-grade inflammation characterized by elevated levels of circulating cytokines and acute phase proteins and excess of adipokines in adipose tissue. Bariatric surgery, important treatment for morbid obesity, has among its positive effects the improvement of inflammatory profile promoted by the reduction of adipose tissue. However, this procedure leads to changes in the gastrointestinal anatomy and physiology and, consequently, alters the absorption process, which may result in micronutrient deficiencies such as vitamins and minerals. It is known that several micronutrients may contribute to the reduction of obesity-related disorders due to the ability to regulate gene expression, modulate adipogenesis and inflammation. In this context, the present study aimed to evaluate the relationship between micronutrient intake, the expression pattern of IL-6, IL-10 and TNF-α genes and the profile of circulating plasma cytokines in women with morbid obesity (n = 30) before and after dietary supplementation with vitamins A, B6, B12, C, D3, and E, folic acid, iron, selenium, zinc, and bariatric surgery. The data showed that only vitamin D3 and C serum concentrations were detected below reference values after supplementation and bariatric surgery. The circulation levels of TNF-α, VEGF and MCP-1 cytokines were significant higher in obese women compared to normal weight women, confirming the inflammatory state associated with obesity. IL-6, TNF-α and VEGF circulation levels were significant decreased after bariatric surgery. Gene expression data also showed ...